AUDIT INTERNAL ATAS KUALITAS PELAPORAN KEUANGAN - Anggraeni, Dwi (Journal of Accounting Taxing and Auditing (JATA), 2024)
AbstractThe purpose of this research is to determine the implementation of internal audits at Ketapang Community Health Centers to determine the quality of financial reporting, and to determine the influence of internal audits on the quality of financial reporting. This research is based on information that the results of the audit carried out by the Banjar City Inspectorate regarding financial reporting received a Fair With Exceptions (WDP) opinion. The data analysis method used in this research is a quantitative analysis method, where to achieve the research objective, namely analyzing the influence of internal audit on the quality of financial reporting, is by using simple regression analysis. The research results show that the implementation of internal audits and the quality of financial reporting at the Ketapang Community Health Center is very good. In line with the hypothesis and previous research, the test results show that there is a significant influence of internal audit on the quality of financial reporting Keywords: Internal audit, quality of financial reporting  AbstrakTujuan dari penelitian ini adalah untuk mengetahui pelaksanaan audit internal di Puskesmas ketapang untuk mengetahui kualitas pelaporan keuangan, dan untuk mengetahui pengaruh audit internal terhadap kualitas pelaporan keuangan. Penelitian ini didasarkan adanya informasi bahwa hasil audit yang dilakukan oleh inspektorat kota banjar terhadap pelaporan keuangan mendapatkan opini Wajar Dengan Pengecualian (WDP). Metode analisis data yang dipakai dalam penelitian ini adalah metode analisa kuantitatif, di mana untuk mencapai tujuan penelitian yaitu menganalisis pengaruh audit internal terhadap kualitas pelaporan keuangan adalah dengan menggunakan analisis regresi sederhana. Hasil penelitian menunjukan bahwa pelaksanaan audit internal dan kualitas pelaporan keuangan di Puskesmas ketapang sudah sangat baik. Sejalan dengan hipotesis danpenelitian terdahulu, hasil pengujian menunjukan bahwa terdapat pengaruh yangsignifikan audit internal terhadap kualitas pelaporan keuangan Kata Kunci : Audit internal, kualitas pelaporan keuangan